A educação estética de Friedrich Schiller - Hipolito de Assis, Adriana Carolina (Revista de Literatura, História e Memória, 2024)
This work aims to show the main ideas of F. Schiller in The aesthetic education of man. The philosopher intended in his work to free man through aesthetic education, since “art is the daughter of freedom”. Schiller believed that this maxim was fundamental to the construction and formation of better human beings. Schiller's aesthetic education proposes to give form (bild), gestalt to the formation of man. Schiller's letters reflect this desire to build an aesthetic education that reconciles reason guided by Kantian philosophy and ludic sensibility, through play.